A Effect of Straw and Cattle Manure Ratio on Bokashi Quality Based on C/N Balance and Nutrient Availability - Yason Edisson Benu; Jemseng Carles Abineno; Marvin Jecson Pandu; Johny Agustinus Koylal; Micha Snoverson Ratu Rihi (The University of Lampung, 2026)
Bokashi is an anaerobically fermented organic fertilizer whose quality depends on the balance between carbon-rich and nitrogen-rich feedstocks. This study evaluated five bokashi formulations prepared from different proportions of leaf straw (JD) and cattle manure (PK), namely: JD100, JD75PK25, JD50PK50, JD25PK75, and PK100. Bokashi was fermented under anaerobic conditions for 21 days and assessed for temperature, moisture content, pH, organic carbon, C/N ratio, total nitrogen, P₂O₅, K₂O, and magnesium (Mg). The experiment was arranged in a Completely Randomized Design, while treatment performance was evaluated using descriptive statistics, including mean ± standard deviation, coefficient of variation, and trend analysis. Results showed that increasing the proportion of manure generally enhanced nutrient availability. Total nitrogen increased from 1.54% in JD100 to 2.72% in JD25PK75, while Mg concentration increased from 3,506 mg kg⁻¹ in JD100 to 10,999 mg kg⁻¹ in PK100. In contrast, straw-dominated formulations maintained higher organic carbon content (27.86%) and more neutral pH conditions (7.7). The C/N ratio declined from 18.10 in JD100 to 8.72 in PK100, indicating greater decomposition and compost maturity. Among the treatments, JD50PK50 exhibited comparatively balanced characteristics, combining relatively high organic carbon, moderate nutrient levels, near-neutral pH (6.8), and a moderate C/N ratio (11.48). These findings suggest that balanced straw–manure mixtures can improve bokashi maturity, nutrient retention, and chemical stability for sustainable organic fertilizer production.